Beneficial Role of ROS in Cell Survival: Moderate Increases in H2O2 Production Induced by Hepatocyte Isolation Mediate Stress Adaptation and Enhanced Survival - Izak Patrik Miller; Ivan Pavlović; Borut Poljšak; Dušan Šuput; Irina Milisav (MDPI AG, 2019)
High levels of reactive oxygen species (ROS) can lead to impairment of cell structure, biomolecules’ loss of function and cell death and are associated with liver diseases. Cells that survive increased ROS often undergo malignant transformation. Many cancer cells tolerate high levels of ROS. Here we report a transiently increased production of H2O2 and concomitant upregulation of antioxidative enzymes triggered by hepatocyte isolation; the H2O2 levels revert in about two days in culture. Three-day survival rate of the isolated cells in the presence of 2.5-fold increase of H2O2 is almost 80%. Apoptosis activation through the mitochondrial pathway is meanwhile reduced by inhibition of caspase-9 triggering. This reduction depends on the amount of H2O2 production, as decreased production of H2O2 in the presence of an antioxidant results in increased apoptosis triggering. These stress adaptations do not influence urea production, which is unchanged throughout the normal and stress adapted phases. We conclude that hepatocytes’ stress adaptation is mediated by increased ROS production. In this case, high ROS improve cell survival.